Counseling About Menopause Complaints in Simbolon Village, Padang Bolak District, Padang Lawas Utara Regency Year 2022 - Harahap, Ica Fauziah; Ratna Wulandari; Yeni Zahara; Melia Sintia Mutiara Pohan (PT Inovasi Pratama Internasional, 2022)
Menopause is phase final where A woman's menstrual bleeding stops completely. syndrome menopause experienced by many woman almost in whole world. Women who will experience menopause will experience symptoms or signs such as depressed mood, anxiety, decreased well-being and sleep disturbances. Factors causing menopause are caused by changes in the production of the hormones estrogen and progesterone, age at menarche , parity and contraception. The purpose of this study was to determine the knowledge of women about menopause complaints in Simbolon Village. This type of research is quantitative in nature by using a descriptive research design . The population in this study were all women aged 45-55 years who live in Simbolon Village totaling 56 people with a total sampling technique, where the entire population was used as the research sample. The results of the study showed that the majority of respondents had sufficient knowledge about menopause complaints as many as 22 people (39.3%) and a minority of less knowledge as many as 16 people (28.6%). It is expected that respondents to actively seek information about complaints during menopause.